Zločin genocida u pravu o odgovornosti: Pojedini aspekti njegova dokazivanja / The Crime of Genocide in Law of Responsibility: Certain Aspects of Proving it: POJEDINI ASPEKTI NJEGOVA DOKAZIVANJA / CERTAIN ASPECTS OF PROVING IT - Omerović, Enis (Pregled: časopis za društvena pitanja / Periodical for social issues, 2023)
The paper deals with the issue of the responsibility of the main subjects of international law for grave breaches of obligations arising from the imperative norms of general international law in relation to the commission of the crime of genocide. The focus of this paper is in certain aspects of the relationship between individual criminal responsibility and the international responsibility of States and international organizations, which should be interpreted as two separate systems of responsibility in international law. Each system has its own special fundaments, features and characteristics. Consequently, the starting point is that the responsibility of States for genocide does not depend on the responsibility of individuals for the crime, although the International Court of Justice has made extensive use of the conclusions of the chambers of the International Criminal Tribunal for the former Yugoslavia. (Judgment from 2007). The paper therefore analyzes the question of the existence of a theoretical legal possibility for the so-called indirectly proving the responsibility of States (and international organizations) for genocide through a prior examination of the criminal responsibility of leaders, but also through proving a joint criminal enterprise for the purposes of committing the crime, or do these conceptions represent a starting point for the responsibility of the main subjects of international law or they are simply "proof" of the attribution of the act to a State? In this paper, we examine whether a joint criminal enterprise could be a reflection of a State plan and/or policy for committing the crime of genocide and how a collective plan or policy for committing that crime could be interpreted. After all, are they actually a dolus specialis of this crime, that is, whether a genocidal intent is manifested in a State precisely in a plan or policy?